Features of Epoxidation of Fatty Acid Methyl Esters in a Bubble Reactor; Journal of Surfactants and Detergents; Vol. 23, iss. 6 - Ivanchina E. D. Emiliya Dmitrievna; Ivashkina E. N. Elena Nikolaevna; Dolganova I. O. Irena Olegovna; Dolganov I. M. Igor Mikhaylovich; Solopova A. A. Anastasia Alexandrovna; Pasyukova M. A. Mariya Alekseevna (2020, 2020)
Title screen